2014
DOI: 10.3389/fnana.2014.00094
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure of synapses on dendritic spines

Abstract: Camillo Golgi’s “Reazione Nera” led to the discovery of dendritic spines, small appendages originating from dendritic shafts. With the advent of electron microscopy (EM) they were identified as sites of synaptic contact. Later it was found that changes in synaptic strength were associated with changes in the shape of dendritic spines. While live-cell imaging was advantageous in monitoring the time course of such changes in spine structure, EM is still the best method for the simultaneous visualization of all c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 64 publications
(107 reference statements)
1
21
0
Order By: Relevance
“…An emerging idea in shape regulation of signaling is the role played by organelles such as the endoplasmic reticulum and nucleus [53,87]. In the case of spines, the spine apparatus is thought to play a critical role in governing synaptic plasticity [42][43][44][45][46][47][48]. We find that the relative organization of the two membranes, PM and the ER membrane, affect the geometric landscape through both shape and boundary condition effects.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An emerging idea in shape regulation of signaling is the role played by organelles such as the endoplasmic reticulum and nucleus [53,87]. In the case of spines, the spine apparatus is thought to play a critical role in governing synaptic plasticity [42][43][44][45][46][47][48]. We find that the relative organization of the two membranes, PM and the ER membrane, affect the geometric landscape through both shape and boundary condition effects.…”
Section: Discussionmentioning
confidence: 85%
“…It is generally accepted that changes in dendritic spine calcium levels, as well as localized protein synthesis, play a central role in structural plasticity, and these two processes may be influenced by the presence and shape of a spine apparatus. Experimental observations have shown that mice lacking spine apparatus (synaptopodin-deficient mice) show deficits in LTP and impaired spatial learning, thus supporting the hypothesis that the spine apparatus is involved in synaptic plasticity [42][43][44][45][46][47][48]. Furthermore, it has been hypothesized that computational modeling of the processes underlying structural plasticity could help to identify the regulatory feedback that governs the switch between LTD and LTP in ER-containing spines [49].…”
Section: Introductionmentioning
confidence: 87%
“…Thorny excrescences are large and complex spines or spine-like structures, often highly branched; they can contain mitochondria, multivesicular bodies, ribosomes, and occasional microtubules–structures that generally are excluded from spines, and they often have a spine apparatus, a structure typically found also only in some large spines (Hamlyn 1962; Frotscher et al 1991; Chicurel and Harris 1992; Petralia and Wenthold 1992; Johnston and Amaral 2004; Petralia et al 2015; Wiera and Mozrzymas 2015). Induction of long-term potentiation in slice cultures can increase the formation of invaginating processes from the excrescences into the mossy terminal; typically, these form new synaptic active zones on the sides of the new “finger-like extensions” (Zhao et al 2012; also reviewed in Frotscher et al 2014, Wiera and Mozrzymas 2015). This circuit may be key to the higher abilities of mammals for pattern separation of episodic memory (Treves et al 2008; Schmidt et al 2012).…”
Section: The Predominance Of the Non-invaginating Dendritic Spine Synmentioning
confidence: 99%
“…The basic structure of synaptic spines was established early in evolution and appears to be roughly the same in all animal groups, but they have been studied best in mammals. Typical spines have a head and narrower neck region and project from the sides of dendrites (Gray 1959; Coss and Perkel 1985; Peters et al 1991; Harris and Kater 1994; Sorra and Harris 2000; Harris and Weinberg 2012; Frotscher et al 2014) (Fig. 1); spines also may project from a neuron cell soma (Peters et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Thereafter, TEM of brain samples has been an essential approach for observing fine synaptic structures including presynaptic vesicles, post-synaptic density, synaptic cleft, mitochondria, smooth endoplasmic reticulum, spine apparatus, and polyribosomes (Frotscher et al, 2014;Steward & Levy, 1982). In addition, by means of the electron microscopy (EM)'s superior resolving power to identify and trace individual axons and dendritic processes in densely packed neuropil, substantial attempts has been made to reconstruct neuronal circuitry in both physiological and neuropathological conditions (Kim et al, 2014;Lee et al, 2005aLee et al, , 2005bLee et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%